The Relationship between Macroeconomic Factors and Indian Stock Market - M.L. , Dr.Ashoka; Keihani, Hamid Reza (The journal of contemporary issues in business and government, 2021)
The main aim of the study to examine the impact of the macroeconomic variables i.e. inflation and exchange rate on the Indian stock market especially on National Stock Exchange (NSE) – Nifty 50 index, the data used for the period from 2010 to 2020 based on the secondary data collected from NSE official website to evaluate the relationship with inflation and exchange rate. Linear regression model was designed and used to evaluate whether independent variables i.e inflation, oil price and GDP growth rate has significant relationship on dependent variable stock market or not. The regression results of the study reveal that there is a statistical negative relationship between inflation and the Indian stock market and whereas, oil price and GDP growth rate has a statistically significant positive relationship on Indian stock market growth.